Breast microbiome associations with breast tumor characteristics and neoadjuvant chemotherapy: A case-control study - Li, Xuejun; Sun, Xiaohu; Zhang, Ai; Pang, Jing; Li, Yun; Yan, Mengfan; Xu, Zhen; Yu, Yue; Yang, Zhengjun; Chen, Xi; Wang, Xin; Cao, Xu-Chen; et al. (Frontiers in Oncology, 2022)
Background: Commensal microbiota have been proven to colonize the mammary gland, but whether their composition is altered in breast cancer (BC) patients remains elusive. This study intends to explore the breast microbiome differences between benign and malignant diseases and investigate the impact of neoadjuvant chemotherapy (NAC) on the breast microbiota in BC patients. Methods: Breast normal adipose tissues (NATs) were collected from 79 BC patients and 15 controls between July 2019 and November 2021. The BC group consisted of 29 patients who had received NAC and 50 who were non-NAC patients. Participants diagnosed with benign breast disease were recruited as controls. 16S rRNA gene sequencing was used to analyze the bacterial diversity of NATs. Results: The community structure of the NAT microbiome was significantly different between BC and control groups. Proteobacteria decreased (47.40% versus 39.74%) while Firmicutes increased (15.71% versus 25.33%) in the BC patients when compared with that in control tissues. Nine genera were enriched in BC NATs and four genera levels increased in the control group. The associations between differential bacterial genera and breast tumor grade were calculated by Spearman’s correlation. The results showed that tumor grade was positively associated with the relative abundance of Streptococcus and negatively related to Vibrio, Pseudoalteromonas, RB41, and Photobacterium. Moreover, menopause was associated with the microbiota composition change of non-NAC BC patients and related to the significant reduction in the abundance level of Pseudoalteromonas, Veillonella, and Alcaligenes. In addition, NAC was related to the beta diversity of BC patients and associated with the decrease of Clostridium_sensu_stricto_7 and Clostridium_sensu_stricto_2 in postmenopausal patients. Of note, Tax4Fun functional prediction analysis revealed that the metabolic state was more exuberant in the BC group with upregulating of multiple metabolism-related pathways. Conclusion: Our results offer new insight into the relationship between NAC and breast microbiota and help to better characterize the breast microbial dysbiosis that occurs in BC patients. Further epidemiological studies with larger sample size and well-designed animal experiments are required to elucidate the role of breast microbiota in the therapeutic outcome of BC.